Identifikasi Potensi Wisata Kabupaten Muna - Muhammad Ishak Hidayat; Shirly Wunas; Suriana La Tanrang (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2015)
Muna Regency is one of the regencies in Southeast Sulawesi Province and is included in Eastern Indonesia which has the potential of natural resources, especially the tourism sector which has the potential to be developed as one of the sectors that can increase the Original Revenue of the Muna Regency. The purpose of this study is to explain the potential of Napabale beach tourism located in the District of Lohiya, Muna Regency. As well as determining the direction of the concept of developing the potential of Napabale beach tourism Muna Regency. This research uses descriptive research that is providing a clearer picture of a phenomenon or phenomenon through tabulative calculations and statistical analysis by emphasizing data analysis using scientific logic based on facts found in the field. Based on the results of research, Napabale beach attractions have the potential to be developed because it has physical potential that can attract tourists including topography, panorama / unique natural beauty such as hills that surround the beach, tunnels that connect between Napabale beach with the strait of Botun, calm sea waves , Marine Biota, and the socio-cultural potential of the local community. The concept of development in this study is divided into two, namely the concept of physical development and the concept of non-physical development.